Hysteretic bit/rock interaction model to analyze the torsional dynamics of a drill string. (October 2018) - Real, F.F.; Batou, A.; Ritto, T.G.; Desceliers, C.; Aguiar, R.R.
Highlights: Novel hysteretic (non-reversible) bit/rock interaction model. Finite element method and a reduced-order model. Model fitted with field data from a 5 km drill string. Torsional stability map. The hysteretic model affects the stability region. Abstract: The present paper proposes a novel hysteretic (non-reversible) bit/rock interaction model for the torsional dynamics of a drill string. Non-reversible means that the torque-on-bit depends not only on the bit speed, but also on the bit acceleration, producing a type of hysteretic cycle. The continuous drill string system is discretized by means of the finite element method and a reduced-order model is constructed using the normal modes of the associated conservative system. The parameters of the proposed hysteretic bit/rock interaction model is fitted with field data. The non-linear torsional vibration and the stability map of the drill string system are analyzed employing the proposed bit/rock interaction model and also a commonly used reversible model (without hysteresis). It turns out that the hysteretic model affects the stability region of the system.